2008
DOI: 10.1152/ajprenal.90218.2008
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin expands a stromal cell population that can mediate renoprotection

Abstract: Recent studies have demonstrated that erythropoietin (EPO) receptors are expressed on tubular epithelial cells and that EPO can protect tubular cells from injury in vitro and in vivo. Separate studies have demonstrated that marrow stromal cells (MSCs) exert a renoprotective effect in ischemia-reperfusion and cisplatin tubular injury via the secretion of factors that reduce apoptosis and increase proliferation of tubular epithelial cells. In the present study we demonstrate that MSCs express EPO receptors and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…In the present study, we demonstrated that 6 months of 8-OHdG = 8-hydroxydeoxyguanosin, BNP = brain natriuretic peptide, ADMA =asymmetric dimethylarginine, baPWV = brachial ankle pulse wave velocity, IMT = intima-media thickness, SBP = systolic blood pressure, DBP = diastolic blood pressure, PGN = proliferative glomerulonephritis, FGS = focal glomerulosclerosis, ARB = angiotensin II receptor blocker, ACEI = angiotensin converting enzyme inhibitor, CTR=cardio-thracic ratio, IVCD=inferior vena cava dimention therapy with recombinant human EPO significantly reduced urinary protein excretion and the urinary L-FABP level in pre-dialysis CKD patients with anemia, thereby suggesting that EPO exerts renoprotective effects. The levels of urinary 8-OHdG, plasma BNP and serum ADMA were also reduced after 6 months of EPO treatment, suggesting that EPO also exerts an anti-oxidative and cardioprotective effect and improves NO bioavailability.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In the present study, we demonstrated that 6 months of 8-OHdG = 8-hydroxydeoxyguanosin, BNP = brain natriuretic peptide, ADMA =asymmetric dimethylarginine, baPWV = brachial ankle pulse wave velocity, IMT = intima-media thickness, SBP = systolic blood pressure, DBP = diastolic blood pressure, PGN = proliferative glomerulonephritis, FGS = focal glomerulosclerosis, ARB = angiotensin II receptor blocker, ACEI = angiotensin converting enzyme inhibitor, CTR=cardio-thracic ratio, IVCD=inferior vena cava dimention therapy with recombinant human EPO significantly reduced urinary protein excretion and the urinary L-FABP level in pre-dialysis CKD patients with anemia, thereby suggesting that EPO exerts renoprotective effects. The levels of urinary 8-OHdG, plasma BNP and serum ADMA were also reduced after 6 months of EPO treatment, suggesting that EPO also exerts an anti-oxidative and cardioprotective effect and improves NO bioavailability.…”
Section: Discussionsupporting
confidence: 66%
“…EPO ameliorates tubulointerstitial injury in the model of unilateral ureteral obstruction by inhibiting inflammation, interstitial fibrosis and tubular apoptosis (26). Bone marrow stromal cells (BMSC) exert a renoprotective effect in tubular injury via the secretion of factors that reduce apoptosis and increase proliferation of tubular epithelial cells (8). EPO receptors are expressed on the surface of BMSCs and EPO protects BMSCs from cell death induced by serum deprivation and stimulates BMSC proliferation in vitro (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that certain Hif-regulated molecules enhance tissue repair during recovery from AKI. For example, Epo, which is induced in our model, has been shown to accelerate repair in experimental models of both, AKI and CKD (5). Another example is stromal cell-derived factor-1, a HIF-1-induced chemokine, that enhances recruitment of progenitor cells to regenerating tissues (7).…”
Section: Discussionmentioning
confidence: 86%
“…The degree of AKI, extent of fibrosis and organization in repair, dedifferentiation of tubules, and continuing hypoxia through vascular rarefaction all contribute to the insidious progression to CKD (5,31,44,64). EPO has the ability to stimulate growth and differentiation of various lineages of cells, including those of mesenchymal, possibly profibrotic, origin (7,13,15,39,46). To date there have been few reports of the effects of delivery of rhEPO for renoprotection in AKI on any subsequent CKD induction.…”
mentioning
confidence: 99%